Effects of vitamin C local application on ligature-induced periodontitis in diabetic rats - Ayşe Toraman; Taner Arabaci; Zeliha Aytekin; Mevlüt Albayrak; Yasin Bayir (University of São Paulo, 2020)
Abstract Objective: This study evaluated the effects of local vitamin C treatment on tissue advanced glycation end products (AGE), interleukin (IL)-6, 8-hydroxy-2-deoxyguanosine (8-OHdG), and matrix metalloproteinases (MMP)-8 in tissues; serum C-terminal telopeptide fragments (CTX); and alveolar bone loss (ABL) in rats. Methodology: 35 male Sprague Dawley rats were divided equally into five groups: 1) control (C), 2) experimental periodontitis (P), 3) experimental diabetes (D), 4) experimental diabetes and experimental periodontitis (D + P), and 5) experimental diabetes-experimental periodontitis-locally applied vitamin C (D + P + LvitC). Diabetes was induced in rats with alloxan monohydrate, after which periodontitis was induced by ligature placement in the right mandibular first molar teeth for 11 days. In the treatment group, vitamin C was administered locally three times with two-days interval after ligature removal. The animals were sacrificed, and the samples were analyzed histometrically and immunohistochemically. Results: CTX, 8-OHdG, and AGE values significantly decreased in the treatment group compared to the D + P group. IL-6 and MMP-8 values decreased in the treatment group compared to the D + P group, but this is not significant. ABL was significantly reduced by the local delivery of vitamin C. Conclusion: This study reveals that vitamin C treatment may be beneficial to reduce serum CTX and gingival MMP-8 levels, oxidative stress, inflammation, and AGE accumulation in periodontal tissue. Vitamin C may be an immunomodulator and antioxidant locally applied in the treatment of periodontitis to reduce the adverse effects of diabetes in periodontal tissues.